Chiral behavior in rat tail tendon fascicles. (7th November 2017) - Buchanan, Kimberly A.; Lakes, Roderic S.; Vanderby, Ray
Abstract: Ex vivo tendon mechanical behavior has been well described under rotationally constrained uniaxial tensile testing. During standard loading of rat tail tendon (RTT) fascicles, apparent axial twist has been observed. To quantify this behavior, we designed a custom testing setup, utilizing magnetic suspension, to allow unconstrained axial rotation during tensile loading. We characterized the rotational behavior of single and paired RTT fascicles under cyclic loading. We also measured stress relaxation across loading cycles as well as "rotational relaxation". Single fascicle nonlinear stretch-twist coupling is well described by the asymptotic function Δ θ = A ( 1 - e - B ε ) in which fascicles rotated a mean ± 51.1° within about 1% applied axial strain. On average, paired fascicles rotated just over 10° less. Specimen cross-sectional diameter had a noticeable effect on the measured mechanical properties, particularly effective elastic modulus. Such stretch-twist coupling and size dependence cannot be understood via classical elasticity but is predicted by Cosserat (micropolar) elasticity. The current study demonstrates RTT fascicles are chiral based on observed axial load-induced twist. Additionally, our findings support existing research that suggests a helical fascicle structure. Potential consequences of helical substructures, mechanical and biological, merit further investigation.